Mekanisme Hiperglikemia Kronis terhadap Densitas Mineral Tulang - Dwiputri, Maliya Finda; Larasati, TA; Jausal, Annisa Nuraisa; Carolia, Novita (Medula, 2024)
Hyperglycaemia or high levels of glucose in the blood is the hallmark of diabetes mellitus. Diabetes mellitus type 2 (DMT2) significantly impacts bone health, leading to a condition known as diabetic bone disease, characterized by decreased bone mineral density and an increased risk of fractures. This condition arises from metabolic disturbances triggered by hyperglycemia, insulin resistance, and inflammatory factors that compromise bone structure. Research indicates that over 35% of DMT2 patients experience reduced bone density, with approximately 20% meeting osteoporosis criteria. The pathophysiology involves several mechanisms, including the accumulation of advanced glycation end-products (AGEs), which hinder bone formation and increase resorption. Insulin deficiency further exacerbates this issue by impairing osteoblast function and reducing the synthesis of key bone matrix proteins like collagen and osteocalcin. Treatment options such as metformin have shown potential in improving bone health, while other medications like sulfonylureas and SGLT-2 inhibitors may have detrimental effects on bone density. Therefore, careful management of diabetes is essential to mitigate the risks of osteoporosis and fractures in patients with DMT2. Ongoing research is needed to deepen the understanding of diabetic bone disease and optimize treatment strategies to protect bone health in these patients.